Solvometallurgical process for the recovery of rare-earth elements from Nd–Fe–B magnets - Orefice, Martina; Binnemans, Koen (Separation and purification technology, 2021)
[Display omitted] •Nd–Fe–B magnets completely dissolved in pyridinium chloride (PyHCl) within 10 min.•Preliminary roasting of the Nd–Fe–B magnets is not required, just milling.•Leaching in pure PyHCl at 165 °C avoided the consumption of other solvents.•Neodymium and dysprosium were extracted by different concentrations of PC-88A.•High-temperature solvent extraction clearly affects the distribution ratio of iron. The protic ionic liquid pyridine hydrochloride is known to be a non-aqueous solvent for metal oxides, including rare-earth oxides. However, its application in extractive metallurgy and especially in solvent extraction has been so far limited by its miscibility with the aqueous phase. In this paper, molten pyridine hydrochloride (165 °C) was used to dissolve production scrap of Nd–Fe–B permanent magnets to recover the valuable metals neodymium and dysprosium. The Nd–Fe–B scrap powder completely dissolved in just 10 min with a lixiviant–to–solid ratio of 10 g g−1. Afterwards, non-aqueous solvent extraction was performed at high temperature (165 °C) by using molecular extractants (PC-88A) or ionic liquids (Cyphos IL 101). The high temperature lowers the viscosity of the solvents, so that they can be used in undiluted form. Moreover, the high temperature affects the equilibrium constants and, hence, the distribution of the metals between the two phases. In the first stage, 30 vol% PC-88A in p-cymene was used to extract dysprosium(III), whereas in the second stage 100 vol% PC-88A was used to extract most of the neodymium(III). Finally, a mixture of Cyphos IL 101–p-cymene 70:30 (wt.:wt.) was shown to efficiently extract iron(II,III) from the concentrate leachate. A conceptual flowsheet was designed, which included the recycling of the pyridine hydrochloride to lower the costs and the environmental impact of the process.